Differences in gut microbes in captive pangolins and the effects of captive breeding - Jiao, Wenjing; Liu, Lina; Zeng, Zhiliao; Li, Linmiao; Chen, Jinping (Frontiers in Microbiology, 2022)
Intestinal microorganisms are crucial for health and have a significant impact on biological processes, such as metabolism, immunity, and neural regulation. Although pangolin are protected animals in China and listed as critically endangered (CR) level by IUCN, the population of wild pangolins has decreased sharply in recent decades. Captive breeding has been adopted to protect pangolins, but the survival is low due to gastrointestinal infections, diarrhea, and parasitic infections. Studies on intestinal microbes in pangolins may reveal the relationship between intestinal microorganisms and health and assist protection. To explore the relationship between intestinal microorganisms and pangolin health, blood parameters and intestinal microorganisms of 10 pangolins (2 Manis pentadactyla and 8 Manis javanica) were studied at the Shenzhen Wildlife Rescue Center. Intestinal microbial diversity of adult Sunda pangolins (M. javanica) was greater than that of adult Chinese pangolins (M. pentadactyla) and sub-adult Sunda pangolins (M. javanica). Busbage phenotypic prediction results suggested that adult Sunda pangolins occupied more diversity and proportion of microbial species to resist environmental pressure than the others. Correlation between blood parameters and intestinal microorganisms showed that blood parameters had no effect on α diversity but impact β diversity significantly. Due to the captive breeding serum cortisol of pangolins was increased, which may affects immunity and changed the intestinal microbial structure. This study provide a scientific basis for the rescue of pangolins through artificial breeding.